Independence of Size and Distance in Binocular Vision - Kim, Nam-Gyoon (Frontiers in Psychology, 2018)
For too long, the size distance invariance hypothesis (SDIH) has been the prevalent explanation for size perception. Despite inconclusive evidence, the SDIH has endured, primarily due to lack of suitable information sources for size perception. Because it was derived using the geometry of monocular viewing, another issue is whether the SDIH can encompass binocular vision. A possible alternative to SDIH now exists. The binocular source of size information proposed by Kim (2017) provides metric information about an object’s size. Comprised of four angular measures and the interpupillary distance (IPD), with the explicit exclusion of egocentric distance information, Kim’s binocular variable demands independence of perceived size and perceived distance, whereas the SDIH assumes interdependence of the two percepts. The validity of Kim’s proposed information source was tested in three experiments in which participants viewed a virtual object stereoscopically then judged its size and distance. In Experiments 1 and 2, participants’ size judgments were more accurate and less biased than their distance judgments, a finding further reinforced by the results of partial correlation analyses, demonstrating that perceived (stereoscopic) size and distance are independent, rather than interdependent as the SDIH assumes. Experiment 3 manipulated participants’ IPDs, one component of Kim’s proposed variable. Size and distance judgments were overestimated under a diminished IPD, but underestimated under an enlarged IPD, a result consistent with predictions based on participants’ utilization of the proposed information source. Results provide unequivocal evidence against the SDIH as an account of size perception and corroborate the utility of Kim’s proposed variable as a viable alternative for the binocular visual system.